Journal of Electrical Systems and Information Technology - Nour, Mohamed; Moteleb, Mohamed Said Abdel; Kozak, Stefan; Ghali, Fadia; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Journal of Electrical Systems and Information Technology (JESIT) is an international peer-reviewed journal seeking innovation, creativity and novelty in the fields of electrical engineering and information technology. Important topics of interest include computer science, communication, power electronics, artificial intelligence, informatics and renewable energy. JESIT aims to attain the state-of-the-art research in theory and application while simultaneously providing a global platform for scientists and academics to collectively explore developments in the latest trends. The journal publishes high-quality, double-blinded peer-reviewed articles within the scope. Authors are welcome to submit reviews, research articles and letters to the Editor.
Keywords: Mechanical engineering; Engineering; Application software; Artificial intelligence; Renewable energy sources; Mechanical Engineering; Technology and Engineering; Computer and Information Systems Applications; Artificial Intelligence; Renewable Energy